The Use of Environmental Media to Improve Students’ Learning Outcomes and Students’ Activity of Class XI-TKJ of SMKN 1 Semen Kediri - Sri Utami Dwi Harini; Sulistiono Sulistiono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
SMK Negeri 1 Semen Kediri is a newly established school, hence the facilities and infrastructure to support learning activities have not been available yet. This study aims to determine the role of the media of environment to enhance the activity and results of learning science of students of Grade X-TKJ SMK 1 Semen Kediri. The study was conducted as Class Action Research according Kemmis and Taggart (1992) as much as two cycles. Each cycle consists of four stages i.e:  planning, implementation, observation and reflection. The parameters observed in each cycle were cognitive learning outcomes and student activity. Learning outcomes was measured by post-test, whereas students' activity was measured by assessment rubric according Supinah (2009). Media usage environment can improve student learning outcomes than the average 78 in the first cycle to 85 in cycle II, as well as an increasing of the percentage of student activity, i.e. 74% in the first cycle to 8t% in cycle II.Keywords: media, environment, learning outcomes, students’ activities